2002
DOI: 10.2202/1949-6605.1195
|View full text |Cite
|
Sign up to set email alerts
|

In-Person Versus Internet Training: A Comparison of Student Attitudes Toward Homosexuality

Abstract: ❖The present study investigated the influence of training modality on attitudes toward lesbian and gay issues. In a short-term longitudinal design (pre-test, post-test, followup), 87 undergraduate and graduate students were randomly assigned to one of three workshop modalities (In-Person, Internet, Control) following pre-test. Participants completed a post-test immediately after the training and a follow-up assessment three weeks later. Analyses revealed that both modalities (In-Person Training and Internet T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
(35 reference statements)
0
8
0
1
Order By: Relevance
“…Writers have highlighted the unique dilemmas faced by LGBT therapists in both therapy and supervision (Russell, 2006; Russell & Greenhouse, 1997; Satterly & Dyson, 2008). Grove (2009) has recorded the sense of challenge faced by student counsellors on learning about heterosexist oppression, and their acknowledgement that having LGBT friends and colleagues was an invaluable source of learning (see also Grove, 2003; Guth et al, 2005; Milton et al, 2005; Mohr, 2002). She has also observed that students' gay‐affirmative skills and knowledge can remain relatively undeveloped during basic training, even when their expressed attitudes are highly affirmative (see also Mohr, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Writers have highlighted the unique dilemmas faced by LGBT therapists in both therapy and supervision (Russell, 2006; Russell & Greenhouse, 1997; Satterly & Dyson, 2008). Grove (2009) has recorded the sense of challenge faced by student counsellors on learning about heterosexist oppression, and their acknowledgement that having LGBT friends and colleagues was an invaluable source of learning (see also Grove, 2003; Guth et al, 2005; Milton et al, 2005; Mohr, 2002). She has also observed that students' gay‐affirmative skills and knowledge can remain relatively undeveloped during basic training, even when their expressed attitudes are highly affirmative (see also Mohr, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, particularly in the early years of their clinical practice, many counsellors' ability to work with LGBT clients is likely to fall short of this ideal. They may lack sufficient life experience to: appreciate that the difficulties faced by LGBT clients; the coping strategies they use; reflect their experiences of living in a largely homophobic world (Dickey, 1997; Grove, 2003); acknowledge the damage that can be caused by making inadvertent heteronormative assumptions (DeBord, 2007; Walker & Prince, 2010); and be wary of the danger that they could collude with, and reinforce, established heterosexual values (Guth, Lopez, Rojas, Clements, & Tyler, 2005; Milton, Coyle, & Legg, 2005; Mohr, 2002; Mohr, Israel, & Sedlacek, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, many of the older and more recent studies suffer from a number of methodological weaknesses, such as lack of a control or comparison condition (e.g., Bassett et al., ; Chng & Moore, ; Finkel, Storaasli, Bandele, & Schaefer, ; Green, Dixon, & Gold‐Neil, ; Nelson & Krieger, ; Penor Ceglian & Lyons, ; Van de Ven, ), small sample size (e.g., Bassett et al., ; Guth, Lopez, Rojas, Clements, & Tyler, ; Lance, ; Pagtolun‐An & Clair, ), limited follow‐up, if any (e.g., Cotton‐Huston & Waite, ; Finkel et al., ; Penor Ceglian & Lyons, ; Lance, ; Rye & Meaney, ), or nonrandom assignment to condition (e.g., Finken, ; Lance, ; Pettijohn & Walzer, ; Rye & Meaney, ; Serdahely & Ziemba, ; Stevenson & Gajarsky, ).…”
Section: Interventions To Reduce Sexual Stigma and Prejudicementioning
confidence: 99%
“…Furthermore, the subsequent articles are pertinent because they give the reader an indication of how to implement these ideas into a research design, how to describe and discuss their prevalence in terms of research implications, and, overall, demonstrate why these ideas matter. For articles that incorporate the concept of confidence intervals, see Guth, Lopez, & Fisher, 2002;Walker, 2003;and Zheng, Whalen, Ciccone, & Shelley, 2001. For an article that uses power, see Schuh & Shelley, 2001.…”
Section: Resultsmentioning
confidence: 99%